PENGARUH MARKETING PUBLIC RELATIONS TERHADAP LOYALITAS PELANGGAN APLIKASI PESAN ANTAR MAKANAN ONLINE - Olivianita, Munaroh; Anggraini, Rosita (Transpublika Publisher, 2023)
This research aims to determine the influence and magnitude of the influence of ShopeeFood's marketing public relations on customer loyalty in the Kebayoran Baru community, South Jakarta. The main concept of this research is marketing public relations and loyalty. This research uses a quantitative approach with survey methods. The research population is the community in Kebayoran Baru, South Jakarta. The sampling technique is purposive sampling. Data collection was carried out by distributing questionnaires to 101 respondents. The collected questionnaires were calculated using the SPSS statistical test. The techniques used in this testing are validity, reliability, simple linear regression and hypothesis testing. The research results show that variable X (Marketing public relations) and variable Y (Customer loyalty) have a positive value or are very influential with a value of 72.6%.